Voyage of the dogs - Van Eekhout, Greg (New York : Harper, 2018)
Lopside, Champion, Bug, and Daisy have been taken on a voyage into deep space aboard the spaceship Laika to help their humans set up an outpost on a distant planet. They are called the Barkonauts. But when Lopside and the other dogs wake up in their hibernation chambers, ready to complete their mission, they realize the humans are gone and the Laika is failing. Survival seems impossible but Lopside and his friends are Barkonauts. And Barkonauts always complete their mission.
Booklist, August 2018
Kirkus Review, July 2018
5.0
3-6
760L
Keywords: Dogs -- Juvenile fiction; Space flight -- Juvenile fiction; Dogs -- Fiction; Space flight -- Fiction; Science fiction; Fantasy fiction; Action and adventure fiction